2011
DOI: 10.4319/lo.2011.56.6.2265
|View full text |Cite
|
Sign up to set email alerts
|

Physical controls on the spatial evolution of a dinoflagellate bloom in a large lake

Abstract: A set of satellite images of chlorophyll a concentration for Lake Kinneret (Israel) from the period February to April 2007 captured the temporal evolution of horizontal patchiness that developed during the typical spring bloom of the dinoflagellate Peridinium gatunense. Narrow bands of high concentration located adjacent to the shoreline at the start of the bloom were followed by progressive propagation of this high-concentration region from the shoreline toward the center of the lake as the bloom proceeded. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 61 publications
(101 reference statements)
2
7
0
Order By: Relevance
“…0.8 for Approach 1, indicating a good match between model and field results. The RMSE and model skill estimates found in our study are of similar order to results of previous modeling studies (Jin et al 2000;Alexander and Imberger 2009;Ng et al 2011).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…0.8 for Approach 1, indicating a good match between model and field results. The RMSE and model skill estimates found in our study are of similar order to results of previous modeling studies (Jin et al 2000;Alexander and Imberger 2009;Ng et al 2011).…”
Section: Resultssupporting
confidence: 90%
“…The RMSE obtained from Paoha Island (Table 2, Approach 2) are lower than those obtained from Simis Station (Table 2, Approach 3) and similar to those obtained from the three stations, indicating that data from the Paoha Island meteorological station are the most representative for the lake. Similar results are shown by the (Jin et al 2000;Alexander and Imberger 2009;Ng et al 2011). …”
Section: Comparisons Of Observations With Results From Modeling-supporting
confidence: 87%
“…Similarly, local methanogenesis in the epilimnion linked to primary production (Grossart et al ; Tang et al ), a process that is not considered in our model, is one hypothesis to explain the observed shallow CH 4 peaks, with a further possible contribution by lateral transport from littoral zones (Hofmann et al ). In contrast to the fast lateral homogenization in the hypolimnion, the time scale for lateral mixing in the epilimnion of Lake Kinneret is on the order of 2 months (Imberger and Marti ), allowing the formation of horizontal patches of phytoplankton (Ng et al ). Similarly, high local release of CH 4 near the boundaries may cause significant lateral variation in epilimnetic CH 4 concentrations, which cannot be considered in a one‐dimensional model.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed significant differences in overall trends based on land use and eco-region. Ng et al (2011) [225] and Curtarelli et al (2015) [96] both incorporated remotely sensed chl-a data into hydrologic models and found that thermal stratification and mixing were key drivers of algal bloom growth and dispersion. Work done by Rose et al (2017) [147] showed that controls on water clarity move from local to watershed scales during dry and wet years respectively.…”
Section: Pub Year Study Duration Study Scale Study Categorymentioning
confidence: 99%